Ethylenediurea reduces grain chalkiness in hybrid rice cultivars under ambient levels of surface ozone in China - Zhang, Guoyou; Risalat, Hamdulla; Kobayashi, Kazuhiko; Cao, Rong; Hu, Qinan; Pan, Xiaoya; Hu, Yaxin; Shang, Bo; Wu, Hengchao; Zhang, Zujian; Feng, Zhaozhong (Frontiers in Plant Science, 2022)
High concentration of tropospheric ozone (O3) causes crop yield losses, which could be reduced by foliar application of ethylenediurea (EDU). Rice grain appearance is a major quality trait that determines the milling quality, white rice productivity and the market value. Grain chalkiness is one of the common defects that deteriorate the grain appearance in rice due to its negative effects on palatability and milling yield. Whether EDU could reduce grain chalkiness in rice which was usually increased by high concentration of O3 is not clarified. We report the grain chalkiness in 19 rice cultivars (CVs) of three types: indica (6 CVs), japonica (5 CVs) and hybrids (8 CVs), observed in an EDU application experiment in the field in China. The ambient O3 level as expressed by accumulated hourly O3 concentration over the threshold of 40 ppb (AOT40) for 80 days until maturity reached 12.8 ppm h at a near-by monitoring station. Fraction of the chalky grains (FCG) in the hybrid cultivars was 8% lower in EDU than that in the control treatments, whereas no significant effect of EDU on FCG was found in japonica or indica cultivars. The reduction of FCG due to EDU treatment in hybrid cultivars was attributed to the significant reduction of milky white grains followed by that of white belly grains. Thus, the application of EDU could ameliorate the decline of grain appearance quality in hybrid rice by decreasing the FCG and enhancing the fraction of perfect grains (FPG). Moreover, there were significant interactions between the EDU application and rice cultivars, indicating varietal difference in the protection of grain appearance quality by EDU. These results suggest the need for further studies on the mechanisms of the effects of EDU on grain chalkiness.